Assessing the adaptive role of cannabidivarinic acid (CBDVA) in aphid defense in Cannabis sativa - Jacob MacWilliams; Venkatesh Padimi; Olivia Carter; Korey Brownstein; Zachary Stansell; Tyler Gordon; Punya Nachappa (Journal of Cannabis Research)
Abstract Background Cannabis sativa has unique secondary metabolites known as cannabinoids, which include tetrahydrocannabinol (THC) and cannabidiol (CBD) and more than 100 related secondary metabolites. There is increasing evidence that cannabinoids can affect insect fecundity and survival. In this study, we assessed the role of a minor cannabinoid, cannabidivarinic acid (CBDVA) on fecundity and survival of C. sativa-adapted specialist aphid, cannabis aphid (Phorodon cannabis) and non-adapted, generalist aphid, green peach aphid (Myzus persicae). Methods We evaluated a panel of high and low-CBDVA hemp genotypes obtained from the USDA-ARS Hemp Germplasm Collection at the Plant Genetic Resources Unit for cannabis aphid resistance in greenhouse experiments. Trichome measurements were recorded for genotypes with the highest and lowest aphid counts. To confirm the role of CBDVA, we performed artificial feeding assays by supplementing CBDVA in aphid diets in the laboratory. Results We found that cannabis populations were significantly higher (Mean ± SE: 221.57 ± 37.27) on a low-CBDVA genotype compared to a high-CBDVA genotype (12.58 ± 3.53) after 14 days of aphid infestation. The high-CBDVA genotype had significantly more trichomes than the low-CBDVA genotype. Supplementation of CBDVA in artificial diets decreased cannabis aphid fecundity from 109.56 ± 10.01 nymphs on diet control and 52.67 ± 7.79 nymphs on DMSO control to 18.71 ± 5.21 nymphs on 1 mM CBDVA + DMSO supplementation after 4 days. CBDVA + DMSO supplementation decreased green peach aphid fecundity from 72.36 ± 6.82 on diet control and 72.50 ± 3.97 on DMSO control to 11.60 ± 2.60 on 0.5 mM CBDVA after 3 days. Conclusions Our results show that CBDVA has insecticidal activity against cannabis aphids and green peach aphids. CBDVA’s potential as a pure essential oil may be an environmentally sustainable pest management option for organic production systems.